2008
DOI: 10.17221/403-pse
|View full text |Cite
|
Sign up to set email alerts
|

Growth and yield of safflower genotypes grown under irrigated and non-irrigated conditions in a highland environment

Abstract: Producers in highland and semiarid regions have difficulty in increasing diversity in crop rotations due to unfavorable conditions imposed by cool temperatures, inadequate rainfall, and shorter growing periods. In such conditions, safflower appears as a promising alternative because it is cold and drought tolerant. The objective of this study was to determine the responses of the hybrid and open-pollinated safflower genotypes to irrigated and non-irrigated conditions in a highland environment. For this reason,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 15 publications
1
5
0
2
Order By: Relevance
“…The results indicate that increasing the concentration of ethephon had a significant effect(P>0.05) on gradually reducing the plant height in the safflower yield, as the plants that were treated with a concentration of 2000 mg / L (E4) gave the lowest average plant height of 107.60 cm with the comparison treatment in which the average plant height was 123.30 cm The reason for the decrement i in plant height may be due to the action of ethylene liberated from the athephon in the plant tissues, which works to inhibit the transport of auxin in the stem tissues and thus reduce the ability to elongate the stem, as well as it encourages an increase in the size of cells in the horizontal direction and affects the rate of cell division It prevents longitudinal growth as it causes a decrease in the elongation of cells in the sub-apical meristem region, and thus a reduction in stem elongation [10]. These results were similar to what was obtained by [11,12], who indicated that spraying athephon with different concentrations led to a significant decrease in the height of plants wheat.…”
Section: Plant Heightsupporting
confidence: 80%
“…The results indicate that increasing the concentration of ethephon had a significant effect(P>0.05) on gradually reducing the plant height in the safflower yield, as the plants that were treated with a concentration of 2000 mg / L (E4) gave the lowest average plant height of 107.60 cm with the comparison treatment in which the average plant height was 123.30 cm The reason for the decrement i in plant height may be due to the action of ethylene liberated from the athephon in the plant tissues, which works to inhibit the transport of auxin in the stem tissues and thus reduce the ability to elongate the stem, as well as it encourages an increase in the size of cells in the horizontal direction and affects the rate of cell division It prevents longitudinal growth as it causes a decrease in the elongation of cells in the sub-apical meristem region, and thus a reduction in stem elongation [10]. These results were similar to what was obtained by [11,12], who indicated that spraying athephon with different concentrations led to a significant decrease in the height of plants wheat.…”
Section: Plant Heightsupporting
confidence: 80%
“…Safflower (Carthamus tinctorius L.) is one of the most important cold and drought-tolerant oilseed crops (Majidi et al 2011;Öztürk et al 2008). It produces oil rich in polyunsaturated fatty acids that play a vital role in reducing blood cholesterol levels (Velasco and Fernandez-Martinez 2001).…”
Section: Introductionmentioning
confidence: 99%
“…In comparison with other oilseed crops, safflower is a crop with high adaptation ability in regions where winter months are cool and summer months are arid. Especially due to its high tolerance for aridity and moderate tolerance to the cold, it is one of the alternative crops to be utilized in the arid and semi-arid agricultural lands of Turkey, particularly in Eastern Anatolia, South-eastern Anatolia, and Central Anatolia Regions (Baydar and Erbas, 2007;Öztürk, 2008). Even though genotypes with high oil content (above 40%) have been identified thorough germplasm screenings, the oil content of the current safflower cultivars remains far below this level (Johnson et al, 1999).…”
Section: Introductionmentioning
confidence: 99%